Microfluidic synthesis of high-performance violet-to-blue perovskite quantum dots for light-emitting applications - Jing Li; Shuai Zhang; Jiawei Liu; Kezhou Chen; Lele Cao; Chuantong Cheng; Kebin Lin; Tiegen Liu; Lili Hou (Chemical Engineering Journal, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Fine-scale mangrove species monitoring and ecological threshold assessment for coastal management in Quanzhou Bay, China - Siming Chen; Fei Chen; Longhui Niu; Zhong Deng; Kebin Wu; Wenbin Li (Environmental Monitoring and Assessment, 2026)

Transforming steel slag into a soil-like matrix via CO2 sequestration: A strategy for simultaneous waste valorization and carbon emission reduction - Xin Xie; Chen Li; Zhiyuan Ma; Ludan Zhang; Qun Zhao; Jie Li; Senlin Tian; Kebin He (Journal of Environmental Management, 2026)

Rapid growth of secondary organic aerosols via aqueous-phase oxidation due to elevated daytime aerosol water contents - Chunrong Chen; Haixu Zhang; Weijia Yan; Qiang Zhang; Kebin He (Environmental Pollution, 2026)

Astronomical calibration of Oceanic Anoxic Event 2 in the Northeastern Neo-Tethys: Insights into the cause of carbon cycle perturbations - Jianzhen Chen; Pengyuan Zhang; Mingzhen Zhang; Zhifu Wei; Gen Wang; Licheng Guo; YingqinWu; Zengguang Guo; Xueyun Ma; Qian Ming; Gaofeng Kang; Kebin Wei; et al. (Global and Planetary Change, 2026)

Exploring the association between air pollution and urogenital congenital anomalies: a global ecological analysis - Kebin Chen; Hanjun Liu; Tingting Wang; Manjun Luo; Xiaorui Ruan; Mengting Sun; Ziye Li; Jianhui Wei; Jiabi Qin (Environmental Pollution, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Strategic approach to reduce environmental damage by CO2 and air pollution based on Energy-Material-Emission Nexus: Insights from Beijing - Daiwei Ouyang; Qingru Wu; Shuxiao Wang; Kaiyun Liu; Shengyue Li; Yao Li; Xinyun Chen; Kun Wang; Wenhao Wu; Zhaoxin Dong; Yueqi Jiang; Yanning Zhang; et al. (Resources, Conservation and Recycling, 2025)

Features of particle-phase PAHs from traffic emissions using tunnel measurement and urban roadside observation in China - Fei Gao; Zhitao Cai; Zhenyu Luo; Junchao Zhao; Songxin Zheng; Li Wang; Bi Chen; Kebin He; Huan Liu (Environmental Pollution, 2025)

Historical air pollutant emissions and future sustainable pathways of global cement plants - Xizhe Yan; Dan Tong; Zhi Cao; Cuihong Chen; Yaqin Guo; Ruochong Xu; Xinying Qin; Yujia Fu; Yang Liu; Dongsheng Zheng; Kebin He; Qiang Zhang (Resources, Conservation and Recycling, 2024)

Upcycling of polyethylene/polypropylene mixtures promoted by well-controlled multiblock olefin copolymers - Yuze Kang; Hanlin Wang; Fanmao Meng; Shangtao Chen; Bin Du; Zihao Jiang; Jiajia Wu; Kebin Zhang; Huan Gao; Li Pan; Yuesheng Li (Chemical Engineering Journal, 2024)

Mid-infrared superconducting nanowire single photon detector enhanced by overcoupled metasurfaces - Yue Dai; Fengjie Zhu; Kebin Fan; Qi Chen; Labao Zhang; Fei Zhou; Yue Fei; Hang Yuan; Hongkai Shi; Hao Wang; Xiaoqing Jia; Qingyuan Zhao; et al. (Science Bulletin, 2024)

GmCOL4-GmZTL1 interaction co-regulates GmSBH1 to improve seed deterioration under high temperature and humidity stress and affect leaf development - Kebin Mu; Yingjie Shu; Ming Chen; Keke Chen; Yuxin Peng; Huimin Hu; Yingzi Shen; Xi Zhang; Lifang Zhuang; Hao Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Spatiotemporal carbon footprint and associated costs of wind power toward China's carbon neutrality - Ziwen Ruan; Xi Lu; Zihua Yin; Shawn C. Mobley; Chongyu Zhang; Jiaxing Wang; Yan Li; Zhaoyang Kong; Guang Shi; Dan Chen; Kebin He (Resources, Conservation and Recycling, 2024)

VOC and IVOC emission features and inventory of motorcycles in China - Zhining Zhang; Hanyang Man; Junchao Zhao; Wendong Huang; Cheng Huang; Shengao Jing; Zhenyu Luo; Xinyue Zhao; Dawei Chen; Kebin He; Huan Liu (Journal of Hazardous Materials, 2024)

Unveiling the toxic effects, physiological responses and molecular mechanisms of tobacco (Nicotiana tabacum) in exposure to organic ultraviolet filters - Dong Jiang; Guoqun Yang; Li-Jun Huang; Kebin Chen; Yangcan Tang; Xin Pi; Runke Yang; Xia Peng; Chuantong Cui; Ning Li (Journal of Hazardous Materials, 2024)

MEIC-global-CO2: A new global CO2 emission inventory with highly-resolved source category and sub-country information - Ruochong Xu; Dan Tong; Qingyang Xiao; Xinying Qin; Cuihong Chen; Liu Yan; Jing Cheng; Can Cui; Hanwen Hu; Wenyu Liu; Xizhe Yan; Huaxuan Wang; et al. (Science China Earth Sciences, 2024)

Changes in Mental Health and EEG Biomarkers of Undergraduates Under Different Patterns of Mindfulness - Miaoling Luo; Quan Gan; Ziyang Huang; Yunxiong Jiang; Kebin Li; Minxiang Wu; Dongxiao Yang; Heng Shao; Yanmei Chen; Yu Fu; Zhuangfei Chen (Brain Topography, 2024)
The effects of short-term mindfulness are associated with the different patterns (autonomic, audio guided, or experienced and certified mindfulness instructor guided mindfulness). However, robust evidence for reported the impacts of different patterns of mindfulness on mental health and EEG biomarkers of undergraduates is currently lacking. Therefore, we aimed to test the hypotheses that mindfulness training for undergraduates would improve mental health, and increase alpha power over frontal region and theta power over midline region at the single electrode level. We also describe the distinction among frequency bands patterns in different sites of frontal and midline regions. 70 participants were enrolled and assigned to either 5-day mindfulness or a waiting list group. Subjective questionnaires measured mental health and other psychological indicators, and brain activity was recorded during various EEG tasks before and after the intervention. The 5-day mindfulness training improved trait mindfulness, especially observing (p = 0.001, d = 0.96) and nonreactivity (p = 0.03, d = 0.56), sleep quality (p = 0.001, d = 0.91), and social support (p = 0.001, d = 0.95) while not in affect. Meanwhile, the expected increase in the alpha power of frontal sites (p < 0.017, d > 0.84) at the single electrode level was confirmed by the current data rather than the theta. Interestingly, the alteration of low-beta power over the single electrode of the midline (p < 0.05, d > 0.71) was difference between groups. Short-term mindfulness improves practitioners’ mental health, and the potentially electrophysiological biomarkers of mindfulness on neuron oscillations were alpha activity over frontal sites and low-beta activity over midline sites.

Covalent organic framework-based immunosensor to detect plasma Latexin reveals novel biomarker for coronary artery diseases - Xiuzhen Li; Huaibin Wan; Yang Tian; Jingzhu Wang; Shaohua Xu; Kebin Huang; Hong Liang; Ming Chen (Analytica Chimica Acta, 2023)

Comparative genomics studies on the stk gene family in vertebrates: From the bighead carp (Hypophthalmichthys nobilis) genome - Yang Mao; Defeng Li; Rongrong Chen; Caifeng Ma; Junzhi Xiong; Kebin Zhang (Fish & Shellfish Immunology, 2023)

GmUGT73F4 plays important roles in enhancing seed vitality and tolerance to abiotic stresses in transgenic Arabidopsis - Huimin Hu; Peipei Qian; Mengyuan Ye; Kebin Mu; Shuang Wang; Ming Chen; Hao Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Chronic Copper Exposure Induces Hypospermatogenesis in Mice by Increasing Apoptosis Without Affecting Testosterone Secretion - Hanming Chen; Zhenlong Kang; Na Qiao; Gaoyang Liu; Kebin Huang; Xi Wang; Congying Pang; Qiwen Zeng; Zhaoxin Tang; Ying Li (Biological Trace Element Research, 2020)

Spectral and functional studies on siphonaxanthin-type light-harvesting complex of photosystem II from Bryopsis corticulans - Wenda Wang; Xiaochun Qin; Min Sang; Dongqin Chen; Kebin Wang; Rongchen Lin; Congming Lu; Jian-Ren Shen; Tingyun Kuang (Photosynthesis Research, 2013)

Rapid purification of photosystem I chlorophyll-binding proteins by differential centrifugation and vertical rotor - Xiaochun Qin; Kebin Wang; Xiaobo Chen; Yuangang Qu; Liangbi Li; Tingyun Kuang (Photosynthesis Research, 2007)